Cultural Theory: the key thinkers - Edgar, Andrew; Sedgwick,Peter (London, 2002)
Featuring over eighty essays, Cultural Theory: The Key Thinkers is a seminal guide to the literary critics, sociologists, historians, artists, philosophers and writers who have shaped culture and society, and the way in which we view them. Ranging from Arnold to Le Corbusier, from Eco to Marx, the entries offer a lucid analysis of the work of influential figures in the study of cultural theory, making this the perfect introduction for the student and general reader alike.
Keywords: Culture